Kinyongia asheorum sp. n., a new montane chameleon from the Nyiro Range, northern Kenya (Squamata: Chamaeleonidae) - Necas, Petr; Sindaco, Roberto; Kořený, Luděk; Kopečná, Jana; Malonza, Patrick Kenyatta; Modrý, David (Zootaxa, 2009)
A new species of chameleon is described from the humid montane forests on Mt. Nyiro in northern Kenya. The new species is clearly distinct from its congeners by external morphology, especially the gular field with long pointed appendicular scales, and geographical isolation. Based on both the morphology and molecular phylogenetic data, we place the new species into the recently described genus Kinyongia.